2003
DOI: 10.1097/00002030-200302140-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CCR5-Δ32 and CCR2-64I alleles on HIV-1 disease progression

Abstract: The protection against AIDS provided by CCR5-Delta32 is continuous during the course of infection. In contrast, the protection provided by CCR2-64I is greatest early in the course of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 35 publications
1
30
3
Order By: Relevance
“…Other studies have shown correlations between disease progression and the CCR2-64 I/V amino acid substitution and between CCR5 promoter haplotype/haplotype combinations (diplotype) [10,19,[23][24][25][26][27][28]. We were unable to demonstrate any relationship between these diplotypes and the in vitro phenotype; however, these additional analyses may have been limited by the small numbers of individuals in the diplotype in vitro phenotype categories observed in this study.…”
Section: Resultscontrasting
confidence: 67%
“…Other studies have shown correlations between disease progression and the CCR2-64 I/V amino acid substitution and between CCR5 promoter haplotype/haplotype combinations (diplotype) [10,19,[23][24][25][26][27][28]. We were unable to demonstrate any relationship between these diplotypes and the in vitro phenotype; however, these additional analyses may have been limited by the small numbers of individuals in the diplotype in vitro phenotype categories observed in this study.…”
Section: Resultscontrasting
confidence: 67%
“…Although the CCR2-64I polymorphic variant has been reported to be protective in the development and progression of inflammatory diseases such as AIDS (Ioannidis et al, 2001;Mulherin et al, 2003), multiple sclerosis (Miyagishi et al, 2003), and development of breast cancer and cervical cancer (Zafiropoulos et al, 2004;Coelho et al, 2005), in our study this variant seems to be a risk factor for the development of bladder cancer.…”
Section: Discussioncontrasting
confidence: 64%
“…Published data demonstrate a disease-retarding effect of the CCR5 ⌬32/wt genotype in HIV-1-infected individuals (5,17,38,39,45) but are conflicting as to whether ⌬32 heterozygosity is associated with relative resistance to HIV-1 transmission (7,13,14,31,37,49,61). Our findings here demonstrate that a single ⌬32 allele exerts a protective effect against viral transmission only if it occurs combined with the Ϫ2459G allele in the CCR5 promoter region (33,35) on the other chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of these coreceptors, it has become well established that alterations in their gene expression and function can impact HIV-1 disease progression. For example, inheritance of the chemokine receptor (CR) polymorphisms CCR5 open reading frame (ORF) ⌬32, CCR5 promoter Ϫ2459 A-to-G, and CCR2 ORF 190 G-to-A (CCR2-64I) are associated with delayed development of the AIDS in HIV-1-infected patients (4,5,9,14,16,17,20,21,29,33,35,36,38,39,45,53,54). Moreover, individuals homozygous for the CCR5-⌬32 allele, comprising about 1% of the Caucasian population, have strongly reduced susceptibility to R5-dependent HIV-1 infection (7,26,49).…”
mentioning
confidence: 99%